DOES RECEIPT OF PUBLIC LONG-TERM CARE BENEFITS REDUCE CAREGIVERS’ LABOR FORCE COMPREHENSION? - Nitz, L (Innov Aging, 2018)
There are few general public long-term care insurance programs in the United States; developed public programs have been running for decades ind Europe and Japan. A question posed by critics is whether family caregivers reduce their unpaid labor or their labor force participation upon receipt of care benefits for their family care recipient. The German Aging Study collects information on labor force participation, care rendered, public insurance benefits received, and a host of items tapping psychological dispositions, family structure and the like. The data lends itself to three approaches: (1) modeling the caregiver’s work hours as a function of LTC benefits received (for the care recipient), type of care provided, hours of care, attitudinal dispositions, and general satisfaction with ones normal job. (2) Modeling the caregiver’s assessment of the burden of care-giving, again as a function of working hours, type of care, and dispositions. (3) The factor structure of the disposition variables clarifies the relationship among these items and care giving burden. Work hours are reduced by 2.5 hours upon receipt of LTC benefits; male gender, depression, self-efficacy, stress, and positive affect drive work hours up. Perception of care-giving burden appears driven down by age, and satisfaction with work life and up for males. A factor analysis of the disposition variables suggests three themes: efficacy, depression v. optimism, and job satisfaction/stress/negative affect. The role of public LTC benefits is complex: it reduces hours worked, not always significantly, and reduces perceived care-giving burden. Perhaps just what it is supposed to do.